ANALISIS FAKTOR TITIK KRITIS DAN UJI MALACHITE GREEN UNTUK MENENTUKAN STATUS HALAL AYAM POTONG DI TPA KECAMATAN MENES - Marlinda Indriati; Tuti Rostianti Maulani; Uti Nurliawati (International Journal Mathla’ul Anwar of Halal Issues, 2021)
This study aims to analyze the critical point factor and malachite green test to determine the halal status of broiler chickens in chicken slaughterhouses (TPA). Samples were taken from 4 landfills in Menes District. The research was conducted in 3 stages, namely first filling the halal slaughtering quisoner according to the LPPOM MUI standard (2011), with results of 80% in accordance with the halal chicken slaughtering technique. The second stage is the Malachite Green test, which aims to prove whether the process of slaughtering broiler chickens is perfect, seen from the removal of chicken blood which must also be perfect, the data obtained is that blood removal is carried out completely from all samples (negative carcass). The last stage is post-slaughter handling by testing Eacherichia coli microbial contamination. The average value of microbial contamination is 2.6 x 104 cfu / gr with purple colonies on brilliance media, and the amount of e.coli contamination of broiler chicken meat exceeds the maximum limit of Eacherichia Coli microbial contamination (BMCM) of fresh chicken meat is less than 1 x 101 cfu / gr.